2016
DOI: 10.1590/1678-98652016000600016
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional care during prenatal and postpartum periods: A report of experiences in a city on São Paulo's coast

Abstract: The purpose of this study is to present a report of the experiences of the adoption of the Approach to Nutritional Care during Prenatal and Postpartum Periods, resulting from a partnership between the university and the municipal primary health care system of Santos, SP, Brazil. This approach was developed through joint work plans based on the need to incorporate nutritional care into the prenatal and postpartum care. All stages of design and implementation and the results of this strategy were documented in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Multidisciplinary actions developed during the prenatal and postpartum periods strengthen bonds between teams and users, facilitate the care line's implementation, and promote integrality 33 . In keeping with previous studies 26,35 , most of the interviewees reported not having received information about BF during the prenatal period. It is common to have not received any teaching or demonstration of BF by any health team professional, although most dentists have stated that they frequently carry out health education activities with the theme of BF during the prenatal period.…”
Section: Discussionsupporting
confidence: 62%
“…Multidisciplinary actions developed during the prenatal and postpartum periods strengthen bonds between teams and users, facilitate the care line's implementation, and promote integrality 33 . In keeping with previous studies 26,35 , most of the interviewees reported not having received information about BF during the prenatal period. It is common to have not received any teaching or demonstration of BF by any health team professional, although most dentists have stated that they frequently carry out health education activities with the theme of BF during the prenatal period.…”
Section: Discussionsupporting
confidence: 62%
“…Despite the recognition of the multi-causal characteristic of obesity and the social determinants of health, the transversality of actions and the dialogue with the Education and Social Assistance sectors were identified as persistent difficulties. Nonetheless, there has been constructive and effective dialogue between the university and the services provided aiming to achieve comprehensive care in Santos [18,43]. It is worth noting that managing overweight without intersectoral collaboration worldwide has proved to be ineffective [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…As to the positive impact of HV programs during the gestational-puerperal cycle, international studies have pointed to reduced tobacco use among puerperae 34 , improved care and development of the child 36,37 , greater social and psychological support to women and households 37 , and three international [34][35][36] and two national [21][22][23][24][25][26][27][28][29][30][31][32] studies reported increased exclusive breastfeeding was identified up to six months. A multiprofessional team is required to perform postpartum HV, which influences the improvement of the quality of care and nears ties between the team and women/households 21,37,38 .…”
Section: Home Visit As a Postpartum Care Toolmentioning
confidence: 99%